Integrating Strategic Management into Academic Administration: Enhancing Institutional Performance in Universities - Masduki Asbari; Tias Pramono; Gusli Chidir; Dwi Ferdiyatmoko Cahya Kumoro; Ervana Chyrinne (International Journal of Management and Economic Research (IJOMER), 2025)
The evolving complexities of higher education institutions demand innovative governance strategies that integrate strategic management into academic administration. This study explores the conceptual and operational dynamics of such integration and its impact on institutional performance. Employing a qualitative multi-case design across selected Indonesian universities, the research analyzes leadership agency, strategic alignment mechanisms, and digital enablement within academic operations. Data were collected through semi-structured interviews, document analysis, and focus group discussions, and analyzed using thematic content analysis and grounded theory principles. Findings reveal that strategic integration fosters institutional coherence, enhances responsiveness to change, and improves key performance indicators such as accreditation outcomes, research productivity, and stakeholder satisfaction. Leadership plays a central role in mediating strategic intent and administrative execution, while digital tools support transparency and real-time decision-making. Despite structural and cultural barriers—including siloed governance and limited strategic literacy—institutions that adopt participatory and adaptive approaches demonstrate greater strategic maturity. This study contributes to the literature by offering a multi-level framework for embedding strategic management within academic workflows. The model emphasizes the importance of transformational leadership, collaborative planning, and digital infrastructure in achieving strategic coherence. Implications for practice include the need for strategic capacity-building, integrated planning systems, and policy support for institutional alignment. Recommendations for future research include comparative studies across diverse national contexts and longitudinal assessments of strategy-performance linkages.